Acute Ulnar Shortening for Delayed Presentation of Distal Radius Growth Arrest in an Adolescent - Prasad Ellanti; Paul Harrington (Case Reports in Orthopedics)
Distal radius physeal fractures are common in children and adolescents. However, posttraumatic growth arrest is uncommon. The management of posttraumatic growth arrest is dependent on the severity of the deformity and the remaining growth potential of the patient. Various treatment options exist. We present a 17-year-old male with distal radius growth arrest who presented four years after the initial injury. He had a symptomatic 15 mm positive ulnar variance managed with an ulnar shortening osteotomy with the use of the AO mini distractor intraoperatively. To the best of our knowledge, an acute ulnar shortening of 15 mm is the largest reported.